Observational and Theoretical Constraints on First-Order Phase Transitions in Neutron Stars - Chen, Jiarui; Ji, Zuhua (Transactions on Computer Science and Intelligent Systems Research, 2025)
Understanding the equation of state of neutron stars (NSs) is a fundamental challenge in astrophysics and nuclear physics. A first-order phase transition at high densities could lead to the formation of a quark core, significantly affecting NS properties. This review explores observational and theoretical constraints on such transitions from observational effects. X-ray observations, including mass-radius measurements from NICER and spectral features like Quasi-Periodic Oscillations, Cyclotron Resonance Scattering Features and Fast Radio Bursts, provide indirect evidence of EOS modifications. Gravitational wave detections, particularly from binary NS mergers GW170817, constrain tidal deformability and post-merger oscillations, which may carry signatures of phase transitions. Measurements of mass, spin evolution, and glitches, with millisecond pulsars exceeding 2M posing challenges to purely hadronic EOSs. Theoretical models and numerical simulations predict that an FOPT could impact gravitational wave signals, twin-star configurations, and NS cooling. Future advancements, including next-generation gravitational wave detectors, high-precision X-ray telescopes, and improved theoreti-cal modeling, will enhance our ability to probe phase transitions in NSs. A combination of these approaches will provide crucial insights into the existence and properties of deconfined quark matter in NS interiors.